PENERAPAN NILAI INTEGRITAS DAN PERSPEKTIF GENDER DALAM PERILAKU BERETIKA - Mayasari, Iin; Wiadi, Iyus; Maharani, Anita; Pramono, Rini S. (Kinerja: Jurnal Bisnis dan Ekonomi, 2012)
This study aimed to determine the effect of the value of integrity and gender in ethical behavior. This studyuses a framework of ethical theory to explain the personal aspect in infl uencing ethical behavior. Respectivevalues of integrity, gender, and ethical conduct have measurements. Research method used survey by sendingquestionnaires to the active workers in college and banking. This survey was preceded by the implementationof focus group discussion to learn about the value of integrity and understanding of the application of applying agender perspective. The main data obtained by distributing questionnaires to the respondents who worked as alecturer at universities and employees working in banking. The main data obtained by distributing questionnairesto the respondents who worked as a lecturer at universities and employees working in banking. Total of 300questionnaires were distributed. Number of questionnaires were used for further analysis was 278. The resultsshowed that the value of integrity affect ethical behavior for both lecturers and banking employees, but onlygender infl uence on the ethical behavior of employees in banking.Keywords: value of integrity, gender perspective, ethical behavior